Microplasma radiofrequency technology combined with triamcinolone improved the therapeutic effect on Chinese patients with hypertrophic scar and reduced the risk of tissue atrophy - Yu S; Li H (Dove Medical Press, 2016)
Shui Yu, Hengjin Li Department of Dermatology, Chinese People’s Liberation Army General Hospital and Hainan Branch, Sanya, People’s Republic of China Objective: The current study aimed to assess the value of microplasma radiofrequency technology combined with triamcinolone for the therapy of Chinese patients with hypertrophic scar. Methods: A total of 120 participants with hypertrophic scars were enrolled in the current study. Participants were divided into two groups based on sex, and then randomly and evenly divided into four groups (Groups A, B, C, and D). Participants in Group A received microplasma radiofrequency technology combined with triamcinolone. Participants in Group B received microplasma radiofrequency technology combined with normal saline. Participants in Groups C and D received triamcinolone (40 and 10 mg/mL) injected directly into scar. Experienced physicians evaluated the condition of scars according to the Vancouver Scar Scale 1 month before and after the therapy. Results: There was no difference in age, sex, area, height and location of scars, and Vancouver Scar Scale scores before the therapy between any groups (P>0.05 for all). Vancouver Scar Scale scores after the therapy were significantly lower than those before the therapy in all groups (P<0.05 for all). Vancouver Scar Scale scores after the therapy in Group A were significantly lower than those after the therapy in Groups B and C (P<0.05 for all). Vancouver Scar Scale scores after the therapy in Group B were significantly higher than those after the therapy in Group C (P<0.05 for all) and similar to those after the therapy in Group D (P>0.05 for all). Incidences of tissue atrophy after the therapy were significantly lower in Groups A and B than in Group C (P<0.05 for all) and similar among Groups A, B, and D (P>0.05 for all). Conclusion: Microplasma radiofrequency technology combined with triamcinolone improved the therapeutic effect on Chinese patients with hypertrophic scar and reduced the risk of tissue atrophy compared with the use of either microplasma radiofrequency technology or triamcinolone injection alone. Keywords: hypertrophic scar, microplasma radiofrequency technology, tissue atrophy, triamcinolone